The capacitance and charge of agglomerated nanoparticles during sintering. (May 2015) - Cao, Leo N.Y.; Wang, Jing; Fissan, Heinz; Pratsinis, Sotiris E.; Eggersdorfer, Max L.; Pui, David Y.H.
Abstract: The electrical capacitance of aerosol particles indicates their diffusion charging level, which is important for their classification by electrical mobility, precipitation (removal or collection) in electrical fields, and morphology characterization. A minimum potential energy method was used to calculate the electrical capacitance for agglomerates composed of equally sized spherical primary particles (PPs). By discretizing the particle surface using finite spherical elements, as net charge only resides on the surface of an isolated conductor, this method was extended to calculate the capacitance of arbitrarily shaped particles. Based on the capacitance, the charge of these particles was obtained by diffusion charging theory. In addition, the dynamics of capacitance and mean charge of agglomerate during sintering or coalescence (at constant particle volume) to aggregates and finally to compact structures was computed and found in agreement with sparse experimental data. Particle morphology strongly affects the capacitance and mean charge of fractal-like particles. For example, both decreased by 60% upon full coalescence or sintering of an agglomerate consisting initially of 128 PPs. Highlights: A minimum potential energy method to calculate electrical capacitance of particles is modified by discretization and extended to arbitrarily shaped particles. The spatial charge distribution of agglomerates is simulated and charges are located mainly in the periphery. The dynamics of capacitance and mean charge of agglomerate during sintering was computed. Particle morphology strongly affects the capacitance and mean charge of fractal-like particles.